10 views (last 30 days)

Hi,

I have the following equation: V1^2 - V1*V2 - Q*Z = 0

V1 is what I need to find

V2 is a known constant

Q is a known vector with complex values

Z is a known constant

This is what I've tried:

syms V1

eq = V1^2 - V1*V2 - Q*Z;

result = roots(eq);

But I get the result "Empty sym: 0-by-1"

Bastian Arturo Romero Mardones
on 17 Nov 2020

Edited: Bastian Arturo Romero Mardones
on 17 Nov 2020

You can try with solve:

syms V1

eq = V1^2 - V1*V2 - Q*Z;

result = solve(eq,V1);

Bastian Arturo Romero Mardones
on 18 Nov 2020

Now understand, i don't considered Q with a vector. In this case you need to use a loop.

Q = [1+3i 2+2i 3+4i 4+2i]; %Example

V2 = 1; Z = 8;

for i = 1:length(Q)

eq2 = [1 -V2 -Q(i)*Z];

result2 = roots(eq2)

result{i} = result2;

end

sorry :D

In this case you should only change Q by Q (i)

for i = 1:length(Q)

syms x

eqn = x^2 - V2*x - Q(i)*Z; %% Change Q ---> Q(i);

solx = solve(eqn, x);

end

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!
## 0 Comments

Sign in to comment.